#TITLE_ALTERNATIVE# - MUHAMMAD (NIM : 10213021), GHIYAATS
Stock market investment is one of the most popular investment commodity this day. Many investors invest their fortune in more than one emitent to diversify their wealth in a portfolio. To maximize the return of a portfolio and to minimize the risk we could use a model called Markowitz model. One of the method that I used in this research is Simulated Annealing, this method is an implementation of physics in economic field to get optimal value of portfolio weights. This research analyzed on how to optimize portfolio by using simulated annealing and genetic algorithm. Both of this model could be used to make an optimize portfolio wich is better than using stock index as reference. After we compare those method, the result of fitness value from Genetic Algorithm is 0,895 and fitness value from Simulated Annealing is 0,879.